A history of the Economic Freedom Fighters (EFF) in South African politics, 2013-2018 - Soldaat, Mohau Martin (University of the Free State, 2022)
This dissertation uses books, chapters in books, newspaper clippings, internet sources and party documents to locate the Economic Freedom Fighters (EFF) history in South African politics from 2013 to 2018. The dissertation investigates the rationale behind the formation of the EFF and evaluates the political role that the EFF has played in South African politics from 2013-2018. It examines the rationale behind the formation of the EFF, maps the role of the EFF in South African politics, and further evaluates its participation in the 2014 national and 2016 local elections. It further looks into the role of the EFF in parliament and its impact from 2014 to 2018. It concludes that the EFF has played a critical role in South African politics. It illustrates that the EFF has positioned itself in the broader scope of South African politics through its active role in parliament and participation in the 2014 national and 2016 local government elections, respectively. The EFF played a critical role in taking votes from the voting constituencies and others of the ANC. In these two elections (2014 and 2016), the EFF has shown upward mobility, my dissertation compared the two in terms of voter turnout and votes that the EFF got. One noticeable phenomenon is the misuse of democratic centralism, which denies other leaders within the party to appear as equal and as important as Julius Malema.

Dipatlisiso tsena di sebedisa mehlodi e fapaneng, ho kenyeleditswe dikarolwana tsa dibuka, dikarolwana tsa di koranta, mehlodi e phatlaladitsweng ke mokgatlo wa Economic Freedom Fighters (EFF), dibuka, dikananelo tse fapaneng, le mehlodi ya marangrang e le ho leka ho fuputsa karolo ya EFF dipolotiking tsa Afrika Borwa ho tloha ka dilemo tsa 2013-2018. Dipatlisiso tsena di fuputsana le tshusumetso e bileng teng pele mokgatlo wa EFF o ka thehwa. Dilemo tsa pele tse hlano ha esale mokgatlo ona one o thehwe di bile boima haholo ho baetapele ba mokgahlo. Ho fihlella tsena tsohle, dipatlisiso tsena di tla sheba ka botebo karolo ya mokgatlo dikgethong tsa selemo sa 2014 tsa karakaretso le tsa 2016 tsa bomasepala. Ho sa le jwalo, dipatlisiso tsena di tla tswela pele ka ho lekola karolo eo mokgahlo ona oe bapetseng lemong tse hlano tse fetileng palementeng, re tsepamisitse maikutlo ho tsa tsamaiso ya dipuisano ka hare ho palamente. Dipatlisiso tsena di utullutse hore e fela mokgahlo wa EFF o bapetse karolo e kgolo dipolotiking tsa Afrika Borwa dilemong tse hlano tse fetileng. Mokgahlo wa EFF o bapetse karolo e kgolo ho theoleng dikgetho tsa African National Congress (ANC). Makgetlong a mabedi ao mokgatlo wa EFF o nkileng karolo dikgethong, sena se bontshitse kgolo e tsitsitseng. Enngwe ya dintho tseo eleng tlohaba boroko mokgatlong wa EFF, ke hore tsohle tsa mokgahlo di itshetlehile hodima moetapele wa mokgahlo e leng Julius Malema, mme tshebediso e mpe ya puso kapa matla e ka beha mokgahlo ka mosing.
Dissertation (M.A. (History))--University of the Free State, 2022